Diseño de un proceso de producción de papel mediante el aprovechamiento de los residuos de racimos de frutos vacíos (RFV) de la palma africana (Elaeis Guineensis). (2022)
In the degree project “Design of a paper production process through the use of empty fruit bunch waste (EFB) of the african palm (Elaeis Guineensis).” The raw material (EFB) was characterized to determine its properties, such as the percentage of humidity, the percentage of ashes, the percentage of cellulose, the solubility in benzene alcohol and the percentage of lignin, it was also carried out The process of obtaining the pulp was carried out by means of soda paste, where the yield, percentage of alpha cellulose, number of kappa and the percentage of lignin were analyzed. Additionally, the bleaching of the pulp with hydrogen peroxide and the formation of the paper were carried out. It is important to highlight that the different samples of paper obtained were subjected to different tests to determine the grammage, thickness, whiteness and porosity.